7.DEFICIENCY OF SERUM 25-HYDROXYVITAMIN D IN PATIENTS WITH BREAST CANCER IN IRAQ (Iraqi Journal of Medical Sciences, 2019)
Background: Many studies defined the association between vitamin D and breast cancer. The relation between human epidermal growth factor receptor 2 (Her2/nue), estrogen or progesterone receptors and vitamin D in breast cancer patients was not clear, since few studies was conducted.Objective: To find out the association of deficiency of vitamin D and breast cancer. The effect of Her2/neu, estrogen, and progesterone receptors on vitamin D in the breast cancer patients was also studied.Methods: Forty patients with benign breast lump as a control group and 40 patients with breast cancer early diagnosed were included in the study. Blood samples (5 mL) were taken from the control and patient groups and analyzed for serum 25-hydroxyvitamin D by using chemiluminescent immunoassay technology. Serum cancer antigen (CA15-3) was measured by using monoclonal antibodies against CA15-3. HER2/neu, estrogen and progesterone receptors were determined in breast cancer patients by immunochemical method.Results: Serum vitamin D in the breast cancer patients before surgery was significantly lower (p ? 0.05) than that in the control group. Preoperatively, serum CA15-3 in Her2/neu positive patients was significantly (p ? 0.05) higher than that in Her2/neu negative patients. Postoperatively, serum CA15-3 in Her2/neu positive patients was not significantly different from that in Her2/neu negative patients. Serum vitamin D, after surgery, in Her2/neu positive patients was not significantly different from that in Her2/neu negative patients. Serum vitamin D was not significantly different in estrogen and progesterone positive patients from that in estrogen and progesterone negative patients, respectively.Conclusion: Severe deficiency of vitamin D was noticed in breast cancer patients in Iraq, and mild deficiency in benign subjects. Serum CA15-3 was higher in positive Her2/neu than negative patients before operation. Her2/neu, estrogen and progesterone positive receptors have no effect on serum vitamin D level in breast cancer patients.Keywords: Vitamin D, breast cancer, CA15-3, Her2/neuCitation: Al-Saigh THT. Deficiency of serum 25-hydroxyvitamin D in patients with breast cancer in Iraq. Iraqi JMS. 2018; 16(4): 400-404. doi: 10.22578/IJMS.16.4.7
Keywords: Vitamin D; breast cancer; CA153; Her2neu